UniEuk: Time to Speak a Common Language in Protistology!. (21st April 2017) - Berney, Cédric; Ciuprina, Andreea; Bender, Sara; Brodie, Juliet; Edgcomb, Virginia; Kim, Eunsoo; Rajan, Jeena; Parfrey, Laura Wegener; Adl, Sina; Audic, Stéphane; Bass, David; Caron, David A.; et al.
Abstract: Universal taxonomic frameworks have been critical tools to structure the fields of botany, zoology, mycology, and bacteriology as well as their large research communities. Animals, plants, and fungi have relatively solid, stable morpho‐taxonomies built over the last three centuries, while bacteria have been classified for the last three decades under a coherent molecular taxonomic framework. By contrast, no such common language exists for microbial eukaryotes, even though environmental '‐omics' surveys suggest that protists make up most of the organismal and genetic complexity of our planet's ecosystems! With the current deluge of eukaryotic meta‐omics data, we urgently need to build up a universal eukaryotic taxonomy bridging the protist ‐ omics age to the fragile, centuries‐old body of classical knowledge that has effectively linked protist taxa to morphological, physiological, and ecological information. UniEuk is an open, inclusive, community‐based and expert‐driven international initiative to build a flexible, adaptive universal taxonomic framework for eukaryotes. It unites three complementary modules, EukRef, EukBank, and EukMap, which use phylogenetic markers, environmental metabarcoding surveys, and expert knowledge to inform the taxonomic framework. The UniEuk taxonomy is directly implemented in the European Nucleotide Archive at EMBL‐EBI, ensuring its broad use and long‐term preservation as a reference taxonomy for eukaryotes.